Canonical correlation analysis on the association between pulmonary function and obesity in early-onset COPD: CT-based body composition analysis - Shi, Jiaru; Li, Tianye; Chen, Zhenghao; Su, Luoman; Wu, Qiongyan; Zhao, Hongjun; Chen, Chengshui (Frontiers in Medicine, 2025)
BackgroundWhile body composition impacts pulmonary function, the differential effects of visceral (VAT) vs. subcutaneous adipose tissue (SAT) in early-onset COPD remain unquantified.ObjectiveTo elucidate the relationship between obesity patterns and pulmonary function in early-onset COPD versus non-COPD populations, focusing on body mass index (BMI), visceral adipose tissue (VAT), and subcutaneous adipose tissue (SAT) distribution.MethodsThis retrospective cohort study analyzed 290 patients (144 early-onset COPD, 146 non-COPD) aged 20–50 years. Body composition (BMI, SAT, VAT) was quantified via CT at the L1 vertebral level. Pulmonary function was assessed by bronchodilator responsiveness testing (FEV₁/FVC, MEF₇₅, MEF₅₀, MEF₂₅). Canonical correlation analysis (CCA) was used to evaluate the multidimensional associations between body composition and pulmonary function.ResultsCanonical correlation analysis revealed distinct multidimensional relationships between body composition and pulmonary function across study cohorts (p < 0.05). In the early-onset COPD cohort (N = 144), a statistically significant canonical variate (r = 0.383, λ = 0.172) demonstrated moderate association strength linking body composition (X1: BMI, SAT, VAT) with pulmonary function (Y1: FEV1, FVC, MEF75, MEF25). Conversely, the non-COPD group (N = 146) exhibited stronger canonical correlation (r = 0.537, λ = 0.405), with body composition (X2: BMI, VAT) associating with pulmonary function (Y2: FEV1, FVC).ConclusionIn summary, early-onset COPD patients with elevated BMI and VAT but reduced SAT exhibited improved pulmonary function across most parameters. This enhancement was not observed in MEF50 and MEF25. In contrast, the non-COPD cohort exhibits overall respiratory enhancement, as the cross-loading coefficient of MEF25—an indicator reflecting the weight of a variable in contributing to the canonical variate—is extremely small (0.05) and has a negligible impact on the overall association.